Magnesium Oxide/Poly(l‐lactide‐co‐ε‐caprolactone) Scaffolds Loaded with Neural Morphogens Promote Spinal Cord Repair through Targeting the Calcium Influx and Neuronal Differentiation of Neural Stem Cells (Adv. Healthcare Mater. 15/2022). Issue 15 (3rd August 2022) - Xie, Jile; Li, Jiaying; Ma, Jinjin; Li, Meimei; Wang, Xingran; Fu, Xinya; Ma, Yanxia; Yang, Huilin; Li, Bin; Saijilafu
Abstract : Spinal Cord Injury In article number 2200386, by Bin Li, Saijilafu, and co‐workers, a novel purmorphamine (PUR)/retinoic acid (RA)‐loaded MgO/PLCL scaffold for repairing spinal cord injury is developed. The magnisum ions released from MgO nanoparticles protect the neurons and the PUR/RA promotes the recruitment and neuronal differentiation of endogenous neural stem cells.